Penerapan Senam Aerobic Low Impact terhadap Tekanan Darah pada Penderita Hipertensi - Mery Rotua Ginting; Aniska Indah Fari; Lilik Pranata; M.Kus Fitriani Fruitasari (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a condition characterized by an increase in blood pressure, defined as systolic values ≥ 140 mmHg or diastolic values ≥ 90 mmHg, and it remains one of the most common health problems experienced by the elderly. Non-pharmacological approaches such as low-impact aerobic exercise are recommended, as this type of exercise is performed at a low to moderate intensity for 20–50 minutes, three times a week. It has been shown to strengthen and maintain the functions of the heart, lungs, blood circulation, muscles, and joints, thereby contributing positively to the management of high blood pressure. This study aims to determine the effect of low-impact aerobic exercise on blood pressure among elderly patients with hypertension through the application of evidence-based practice. A quantitative case study approach was employed to gain a deeper understanding of changes in blood pressure following the intervention. Three elderly respondents diagnosed with hypertension were involved and instructed to perform low-impact aerobic exercise for three consecutive days. The results showed a decrease in blood pressure among all respondents, although the outcomes varied. The first respondent experienced changes from 140/80 mmHg to 130/70 mmHg and 130/90 mmHg, the second respondent from 150/90 mmHg to 160/80 mmHg and then 150/70 mmHg, and the third respondent from 150/80 mmHg to 110/70 mmHg and 130/70 mmHg. These findings indicate that low-impact aerobic exercise has a positive effect in reducing blood pressure, despite some variability between individuals. In conclusion, low-impact aerobic exercise is proven to help control blood pressure in hypertensive patients. This study highlights the importance of encouraging hypertensive individuals to adopt regular and independent low-impact aerobic exercise as a simple strategy to maintain stable blood pressure and improve overall quality of life.